2008
DOI: 10.1111/j.1601-183x.2008.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of febrile seizures and febrile seizure susceptibility in mouse inbred strains

Abstract: Febrile seizures (FS) are the most prevalent seizures in children. Although FS are largely benign, complex FS increase the risk to develop temporal lobe epilepsy (TLE). Studies in rat models for FS have provided information about functional changes in the hippocampus after complex FS. However, our knowledge about the genes and pathways involved in the causes and consequences of FS is still limited. To enable molecular, genetic and knockout studies, we developed and characterized an FS model in mice and used it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 34 publications
3
59
0
1
Order By: Relevance
“…In general, transponders measure about 2 mm diameter and 12-14 mm long and their use is not applied in animals younger than 8 -10 pnd or weighing less than 5 g (see example 19 ). Recently, a smaller sized microchip has been launched by Lutronic International (http://www.lutronic.eu/) as an identification method applicable to mice a few days after birth (http://www.rfcafe.com/miscellany/ press_releases/2007/lutronic_intl_6-11-2007.htm).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, transponders measure about 2 mm diameter and 12-14 mm long and their use is not applied in animals younger than 8 -10 pnd or weighing less than 5 g (see example 19 ). Recently, a smaller sized microchip has been launched by Lutronic International (http://www.lutronic.eu/) as an identification method applicable to mice a few days after birth (http://www.rfcafe.com/miscellany/ press_releases/2007/lutronic_intl_6-11-2007.htm).…”
mentioning
confidence: 99%
“…body temperature) without disturbing the animals presents another advantage of this identification technique. 19,21 However, this identification method requires specific equipment and transponders that may be costly, even though they can be reused.…”
mentioning
confidence: 99%
“…For example, high fever often provokes seizures in children. Some studies in recent years have revealed that excitotoxic brain damage and hypoxic hippocampal damage are associated with changes in brain temperature [37]. Experimental studies have demonstrated that electrophysiological epileptiform activity increases as temperature rises, whereas hypothermia reduces ictal discharges.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the strain-dependent differences in warm air stream-induced eFS susceptibility have been reported in mice (29) but not in rats.…”
Section: Animal Models Of Fsmentioning
confidence: 99%